Second stage Lensmen - Smith, E. E. (Edward Elmer), 1890-1965; Rogers, Hubert, 1898-1982 (Salt Lake City, UT : Project Gutenberg, 2023)
"Second Stage Lensmen" by E. E. Smith is a science fiction novel first published in book form in 1953. The fifth volume in the Lensman series follows Kimball Kinnison and an elite cadre of mentally enhanced Lensmen as they continue their war against the mysterious Boskonian organization. When Earth faces devastating attacks, the Lensmen must develop new weapons and strategies. Kinnison's investigation leads to creating Civilization's first female Lensman, Clarissa MacDougall, while he infiltrates deep into enemy territory to uncover Boskone's true power. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Second_Stage_Lensmen
Release date is 2023-04-07
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Space warfare -- Fiction; Telepathy -- Fiction; Life on other planets -- Fiction; Peace officers -- Fiction; Space pirates -- Fiction; Organized crime -- Fiction; Undercover operations -- Fiction